2018
DOI: 10.1109/access.2018.2883690
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of a Chaotic Image Encryption Algorithm Based on Information Entropy

Abstract: Recently, a chaotic image encryption algorithm based on information entropy (IEAIE) was proposed. This paper scrutinizes the security properties of the algorithm and evaluates the validity of the used quantifiable security metrics. When the round number is only one, the equivalent secret key of every basic operation of IEAIE can be recovered with a differential attack separately. Some common insecurity problems in the field of chaotic image encryption are found in IEAIE, e.g. the short orbits of the digital ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(97 citation statements)
references
References 32 publications
0
97
0
Order By: Relevance
“…The specific properties of chaotic systems, such as initial state sensitive dependence, unpredictability, make them widely studied and applied in the field of information security [8]- [12]. These properties are similar to the counterparts of cryptography [9], [10], [22]. In this section, an image encryption scheme based on the proposed Chua's circuits with 19-and 21-segment piecewise-linear Chua's diodes are proposed to verify its merit for image security.…”
Section: Application In Image Secure Communicationmentioning
confidence: 97%
“…The specific properties of chaotic systems, such as initial state sensitive dependence, unpredictability, make them widely studied and applied in the field of information security [8]- [12]. These properties are similar to the counterparts of cryptography [9], [10], [22]. In this section, an image encryption scheme based on the proposed Chua's circuits with 19-and 21-segment piecewise-linear Chua's diodes are proposed to verify its merit for image security.…”
Section: Application In Image Secure Communicationmentioning
confidence: 97%
“…correlation, entropy, histogram variance, Number of Pixel Change Rate (NPCR), Unified Average Changing Intensity (UACI), key sensitivity, robustness against differential attack, sequence test, and NIST randomness test. Considering the quantitative test results of the four special schemes on the metrics, it is concluded that the metrics are far ineffective for security analysis, which are further qualitatively analyzed the inefficiency of the metrics in [1]. Other image cryptanalysis works are separately reviewed in the following three subsections.…”
Section: Survey On Image Cryptanalysis In 2018mentioning
confidence: 99%
“…Security and privacy protection of image data is an everlasting challenge in the cyberspace. Designing image encryption schemes (algorithms, techniques, methods) and further processing in the domain of the cipher-images received intensive attention from researchers in the field of security, signal processing, nonlinear science, and etc [1]. From Web of Science Core Collection, we found about 1,000 publication records published in the year 2018 by inputting "image" and "cryptograph* or encrypt*" in the field of "Topic".…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the authors claimed that the proposed algorithm can be used as a secure and effective communication method for images. However, Li et al [19] reported some security defects of the chaos-based pseudo-random number generator used in this algorithm. Furthermore, they were able to break its one round version completely with a differential attack.…”
Section: Introductionmentioning
confidence: 99%